Coronary CT Angiography - Dewey, Marc (Springer, 2017)
Coronary CT angiography has attained increasing scientific attention at academic institutions and has become a highly accurate diagnostic modality. Extending this knowledge into a practice setting is the purpose of "Coronary CT Angiography". This book will assist you in integrating cardiac CT into your daily practice, while also giving an overview of the current technical status and applications. The specific features of scanners from all four main vendors are also presented providing an objective overview of noninvasive coronary angiography using CT.